Anomalous diffusion of plasma in the lower hybrid cavities observed in the terrestrial ionosphere - Azarenkov, N.A.; Chibisov, D.V. (Вопросы атомной науки и техники, 2018)
The problem of the disappearance of the lower hybrid cavities, which are observed in the terrestrial ionosphere,
is considered. As a possible mechanism which leads to the disappearance of the cavities the anomalous diffusion of
plasma, which occurs due to a drift turbulence of plasma is considered. The frequency and the characteristic time of
development of the drift instability in the cavity, the saturation level of the instability and the anomalous diffusion
coefficient of plasma in the cavity are obtained. The cavity lifetime is also estimated, which can be greater or about
1 second. Розглянуто проблему зникнення нижньогібридних порожнин, які спостерігаються в земній іоносфері. В якості можливого механізму, який призводить до зникнення порожнин, розглядається аномальна дифузія плазми,
що виникає внаслідок її дрейфової турбулентності. Отримано частоту і характерний час розвитку дрейфової
нестійкості в порожнині, рівень насичення нестійкості і коефіцієнт аномальної дифузії плазми в порожнині.
Також оцінюється час життя порожнини, який може становити більше або порядку 1 с. Рассмотрена проблема исчезновения нижнегибридных полостей, наблюдаемых в земной ионосфере. В качестве возможного механизма, приводящего к исчезновению полостей, рассматривается аномальная диффузия
плазмы, возникающая из-за её дрейфовой турбулентности. Получены частота и характерное время развития
дрейфовой неустойчивости в полости, уровень насыщения неустойчивости и коэффициент аномальной диффузии
плазмы в полости. Также оценивается время жизни полости, которое может составлять больше или порядка 1 с.